Efek Kinerja Lingkungan dan Kinerja Sosial Terhadap Kinerja Pasar Perusahaan di Indonesia - Meidiaswati, Harlina; Madyan, Muhammad; Sasikirono, Nugroho (Asosiasi Peneliti Manajemen Adat Indonesia, 2023)
This study examines the effect of environmental performance as measured by the PROPER award rating and social performance as measured by the corporate social responsibility (CSRI) disclosure index on the company's market performance as measured by the Tobin's Q ratio. The sample being used is 188 companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2016. OLS results show that the PROPER award has a positive effect on market performance. Companies that receive prestigious PROPER awards (blue, green or gold) show higher market performance. The test also shows the positive influence of social performance on market performance. Furthermore, social performance fully mediates the effect of environmental performance on market performance. Robustness check using quantile regression shows that social performance fully mediates the effect of environmental performance on firms with small and medium market performance (Q25 and Q50).